Effect of dystocia and treatment with oxytocin on neonatal calf vitality and acid-base, electrolyte and haematological status. Issue 2 (February 2015) - Vannucchi, C.I.; Rodrigues, J.A.; Silva, L.C.G.; Lúcio, C.F.; Veiga, G.A.L.
Highlights Obstetrical condition alters acid-base and electrolyte homeostasis of calves. Dystocia compromises neonatal acid-base balance in calves. Calves born to dams treated with oxytocin have altered oxygenation. Calves born to dams treated with oxytocin have modified sodium balance. Dystocia results in low vitality calves.